Synthesis, spectroscopic characterization and biological analysis of a new palladium(II) complex with methionine sulfoxide - Corbi, Pedro P.; Cagnin, Flavia; Sabeh, Lilian P. B.; Massabni, Antonio Carlos [UNESP]; Costa-Neto, Claudio M. (Elsevier B.V., 2007)
A new palladium(II) complex with methionine sulfoxide was synthesized and characterized by a set of chemical and spectroscopic techniques. Elemental and mass spectrometry analyses of the solid complex fit to the composition [Pd(C5H10NO3S)(2)]center dot H2O. C-13 NMR, [H-1-N-15] NMR and infrared spectra indicate coordination of the amino acid to Pd(II) through the carboxylate and amino groups in a square planar geometry. The complex is soluble in water.Biological activity was evaluated by cytotoxic analysis using HeLa cells. Determination of cell death was assessed using a tetrazolium salt colorimetric assay, which reflects the cells viability. After incubation for 48 h, 20% of cell death was achieved at a concentration of 200 mu mol L-1 of the complex. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: palladium(II); methionine sulfoxide; infrared spectroscopy; N-15 NMR; antitumor; cytotoxicity